Impact of Automated Teller Machine (ATM) Service Quality on Customer Satisfaction in the Nepalese Commercial Banks - Joshi, Chhemanand (Contemporary Research: An Interdisciplinary Academic Journal, 2019)
The aim of this study was to understand the impact of ATM service quality on the customer satisfaction in Nepalese banking sector. This study has used the primary data of customer satisfaction survey (N = 60). The data was collected using a structured questionnaire designed to ascertain the satisfaction levels. Descriptive statistics analysis was used to explain the satisfaction level of respondents. Correlations and multiple linear regression analysis were used to test the hypothesis. The ATM services have positive impact on the customer satisfaction; if proper functioning is ensured by the banks, there will be significantly higher customer satisfaction. Availability of cash has highest impact on customer satisfaction. Next most influencing factor is location of ATM. The study has been carried out primarily in Dhangadhi, Kailali and hence cannot be generalized on all over Nepal. The banks can utilize the finding to improve the services of ATMs and can enhance the overall satisfaction of their customers. The paper has identified, availability of cash as the most influencing significant factor, which the banks may take care to enhance the customer satisfaction.